Optimal moment to change pressure regulator and sprayer kit on center pivot irrigation machines: a theoretical proposal - Leira, Ramón Pérez; Román, Rodrigo Máximo Sánchez [UNESP]; Frizzone, José Antônio [UNESP] (My University, 2011)
A theoretical model was developed in order to determine the optimal moment for substituting the sprayer and pressure regulator kit on a center pivot irrigation machine. The model is based on the hypothesis that pressure regulator and sprayer deterioration decrease irrigation uniformity. To compensate the deficit that happens at under irrigated areas, an increase on irrigation depth is required. The model considers: additional water consumption and energy costs, maintenance and labor costs, as well as yield losses associated with under or over irrigated areas. The sum of all these components is compared to buying and installing a new spray kit cost, allowing the farmer to decide the best moment to renovate the sprayer and pressure regulator kits on a center pivot irrigation machine based on economic criteria.
Keywords: Costs; Efficiency; Irrigation; Mathematical model; Pivot